Association Between Infection History and Complex Nutrition Intake with Wasting Incidence in Toddlers - Utami, Fathia Wianida; Zulaikha, Fatma; Asthiningsih, Ni Wayan Wiwin (Genius Journal, 2025)
Background: Wasting in toddlers is a form of acute malnutrition characterized by rapid weight loss and low weight-for-height z-scores, which can severely impact physical growth and cognitive development. Factors such as a history of infection and inappropriate complementary feeding practices have been identified as potential contributors. Objective: This study aimed to analyze the relationship between infection history and the provision of complementary feeding (MPASI) with the incidence of wasting among toddlers aged 2–5 years in the working area of Sidomulyo Health Center, Samarinda. Method: A cross-sectional study with a quantitative correlational approach was conducted. A total of 168 toddlers were selected using stratified random sampling. Data were collected through structured questionnaires and anthropometric measurements, and analyzed using the Chi-Square test. Results: The results showed that 25.6% of the toddlers experienced wasting. Toddlers with a history of infection were found to be at significantly higher risk, with an odds ratio (OR) of 13.85 (p = 0.000). Additionally, toddlers who received complementary feeding before the age of 6 months were 8.9 times more likely to experience wasting (p = 0.000; OR = 8.9). Both variables showed a statistically significant association with the incidence of wasting. Conclusion: The study found a significant relationship between infection history and complementary feeding practices with the incidence of wasting among toddlers. Strengthening maternal education, timely feeding, and infection prevention is essential to reduce the risk of wasting in early childhood.